Atovaquone/proguanil for the prophylaxis and treatment of malaria. Issue 6 (December 2005) - Patel, Samir N; Kain, Kevin C
Increases in international travel and escalating drug resistance have resulted in a growing number of travelers at risk of contracting malaria. Drug resistance and intolerance to standard agents such as chloroquine, sulfadoxine/pyrimethamine and mefloquine has highlighted the need for new antimalarials. The recently licensed fixed combination of atovaquone and proguanil hydrochloride (Malarone™) is a promising new agent to prevent and treat Plasmodium falciparum malaria. Randomized controlled trials have shown that atovaquone/proguanil is well tolerated and efficacious for the prevention and treatment of drug-resistant P. falciparum malaria. Atovaquone/proguanil is active against the liver stage of P. falciparum malaria parasites and when used as a prophylactic agent it can be discontinued shortly after leaving malaria-endemic areas, offering a clear advantage for drug adherence.